2018
DOI: 10.21474/ijar01/7563
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Attitude Towards Teaching and Learning Ofmathematics in Senior High Schools of Cape Coast Metropolis.

Abstract: The paper explored gender difference in attitude toward teaching and learning of mathematics in Senior High Schools of Cape Coast Metropolis. This subject was conceived from gender biases which could be observed from the West African Senior Secondary Examination (WASSCE) results over time. The study identified five attitudinal factors toward teaching and learning of mathematics: gender interest, gender confidence, gender fear, gender competence and gender success. Descriptive survey design was used coupled abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Also, they view learning the discipline as enjoyable and interesting. This conforms with Martey [40] that the students' high perception is influenced by their recognition of social sciences as a potential factor in developing their nationalism, patriotism, and understanding of their rights and responsibilities as citizens. Further, most students believe that through this subject, they learn to connect with themselves, society, and the world [41].…”
Section: Degree Of Perception In Learning Social Sciencesupporting
confidence: 87%
“…Also, they view learning the discipline as enjoyable and interesting. This conforms with Martey [40] that the students' high perception is influenced by their recognition of social sciences as a potential factor in developing their nationalism, patriotism, and understanding of their rights and responsibilities as citizens. Further, most students believe that through this subject, they learn to connect with themselves, society, and the world [41].…”
Section: Degree Of Perception In Learning Social Sciencesupporting
confidence: 87%
“…Previous studies also suggested that elementary and secondary school pupils view the operation on electricity or the presence of a complex nature as a prerequisite for a technical system (Kumari & Saraladevi, 2014). The high school pupils between the ages of 15 and 17 included in our study were, like previous participants, inclined to think that a technical system should not be controlled manually, but certainly electrically.…”
Section: Conclusion and Discussionmentioning
confidence: 77%
“…With the right instructional materials, such as a thermometer for measuring temperature, and a microscope for viewing very small objects and organisms, the students may be able to grasp the full scope of the concepts in the subject. Instructional materials help teachers to meet individual differences of the learners in the class by using different teaching aids that suit the different senses of the learners (Nartey, 2018). Instructional materials are used to supplement verbal explanations of different concepts or descriptions so that the lesson can be real to the students.…”
Section: Literature Reviewmentioning
confidence: 99%